Characterisation of a novel group B oncolytic adenovirus, ColoAd1 - Di, Y (2011)
Developing high potent oncolytic virus with multimodal antitumour capabilities is crucial for realizing the full potential of oncolytic virotherapy in cancer treatment. ColoAd1 is a novel replicating chimeric group B adenovirus recently bioselected from a large library of recombinant viruse. This thesis aims at evaluating the oncolysis ability of ColoAd1, characterization of its cellular activities and the corresponding responses from host tumour cells, elucidating the killing mechanism as well as exploring its potential applications in the advanced cancer therapy. Among all oncolytic adenoviruses tested, ColoAd1 elicited the strongest cytotoxicity with a rapid killing kinetics in tumour cells. The virus displayed high infection efficiency, enhanced genome replication (compared to other adenoviruses) and strict selectively in tumour cells.The viral oncolysis also induced a bystander killing effect. Investigation of the host cells responses during ColoAd1 oncolysis showed the virus mediated cell killing is not classic apoptosis but rather necrosis-like. The dying cells displayed the early cytoplasmic membrane leakage, falling intracellular ATP with a rise in calcium, disruption of the cell cycle and cellular DNA damage, with rapid release of progeny virions from the cell; on the other hand, ColoAd1-killing lacked the characteristic hallmarks of apoptosis. Autophagy may play a role in final execution of oncolysis but is not the main death mechanism. The cellular pathway involved in ColoAd1 oncolysis was further studied by using a panel of specific inhibitors. The results indicated the ColoAd1 mediated cell death is PARP- and RIP1- dependent and necroptosis could be the major death mechanism. The highly oncolytic potency and special killing mechanism of ColoAd1 may have beneficial implication for advanced cancer therapies, including the possibility of circumventing drug resistance and invoking cancer immunotherapy. The data in this thesis supported ColoAd1 as a novel potent oncolytic virus candidate. It promises to overcome the major drawbacks of Ad5 and therefore could have enhanced therapeutic efficacy in future clinical trial.